EVALUATION OF DISTRIBUTION TRANSFORMER LOADING ON THE AMBON CITY EXPRESS REPEATER - SOLEMAN SESA; JOHANIS TUPALESSY (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2021)
Power system distribution, reliability and stability of the system is very important in order to provide convenience in service to consumers. This can be fulfilled by paying attention to the condition of the existing power equipment. One of the most important equipment in power system operation is transformer. Distribution transformers will work optimally if the electrical load carried in the transformer network area does not exceed the capacity of the distribution transformer. When there is an overload on a transformer, the insulation inside the transformer becomes overheated due to the current loaded on the transformer is very large or exceeds the nominal current of the transformer. The solution to overcome the overload on the transformer is if the location between transformers is far apart, it can be done by inserting the transformer by referring to the transformer rating that will supply the load. If the load supplied by the transformer on the network is getting bigger, then a transformer with a large capacity is used to supply the large load, otherwise the transformer will experience an over load which can cause the transformer to trip. At the KTAEXK007 and KTAEXK009 substations, both load shifting is carried out to one of the nearest transformers, namely the KTAEXK008 Amans Hotel substation. Then in the existing calculations, there are two transformers that will be used for transformer insertion, namely a transformer with a rating of 315 kVA and a 100 kVA transformer.